2017
DOI: 10.4274/tjps.57070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Activities and Phenolic Compounds of <i>Scorzonera latifolia</i> (Fisch. & Mey.) DC. Collected from Different Geographic Origins in Turkey

Abstract: Amaç: Bitkilerin kimyasal içeriği pek çok parametreden etkilenmektedir. Bitkinin toplandığı bölge içerdiği fenolik bileşiklerin kompozisyonunu ve dolayısıyla aktivitelerini etkilemektedir. Bu çalışmada, Türkiye'nin farklı bölgelerinden toplanan Scorzonera latifolia (Fisch & Mey.) DC. kök ve toprak üstü kısımlarının antioksidan etki potansiyallerinin ölçülmesi amaçlanmıştır. Gereç ve Yöntemler: Test edilen ekstrelerin antioksidan kapasiteleri 1,1-difenil-2-pikrilhidrazil (DPPH) radikal süpürücü etkileri ve malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Acikara et al. (2017) found that the methanol/water (80/20) extracts of the aerial parts of S . latifolia showed high DPPH radical scavenging activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acikara et al. (2017) found that the methanol/water (80/20) extracts of the aerial parts of S . latifolia showed high DPPH radical scavenging activity.…”
Section: Resultsmentioning
confidence: 99%
“…Milella et al (2014) suggested that the aerial parts of S. papposa chloroform, chloroform/methanol, and butanol extracts scavenged with a high rate of DPPH radicals. Acikara et al (2017) found that the methanol/water (80/20) extracts of the aerial parts of S. latifolia showed high DPPH radical scavenging activity. In another study, it was determined that compounds obtained from S. divaricata roots scavenged the ABTS and DPPH radicals at a lower rate than standard antioxidant trolox (Yang et al, 2013).…”
Section: Antiradical Propertiesmentioning
confidence: 99%